TATAKELOLA PERUSAHAAN, STRUKTUR KEPEMILIKAN, BOOK TAX DIFFERENCES, DAN PERSISTENSI LABA - Grace Pramana (Jurnal Akuntansi Bisnis, 2016)
This research is aimed to examine the impact of the board of directors, audit committee, book-tax differences, audit quality, managerial ownership and institutional ownership on the earnings persistence of manufacturing companies in Indonesia. According to Hanlon (2005) in Irfan and Kiswara (2013) earnings persistence is the company ability to maintain the current period profit until the next period. Earnings persistence reflects the earnings quality and relevant are used to predict the company's future earnings. This research uses three variables control such as leverage, cash flow volatility, and sales volatility. Total samples used in this research were 212 manufacturing companies which listed in the Bursa Efek Indonesia (BEI) during the period of 2010-2014.Samples were selected using purposive sampling method. Statistical tests in this study using multiple regression. Results of this study found that the audit quality, leverage,and sales volatility significantly affect to earnings persistence, where as board of directors, audit committee, book-tax differences, managerial ownership, institutional ownership, and cash flow volatility didnt have significant affect to earnings persistence.